2018
DOI: 10.1186/s12891-018-2192-6
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain and associated factors among Ethiopian elementary school children

Abstract: BackgroundEthiopian school children often carry school supplies in heavy school bags and encounter limited school facilities. This stresses their vulnerable musculoskeletal system and may result in experiencing musculoskeletal pain. High prevalence of musculoskeletal pain has been documented, but data on musculoskeletal pain among elementary school children in Ethiopia is lacking. To determine the prevalence of musculoskeletal pain and associated factors among elementary school children in Gondar, Ethiopia.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
0
13
0
3
Order By: Relevance
“…Furthermore, it is likely that the key mechanical factor triggering LBP when carrying a schoolbag is not its weight per se, but whether it exceeds the physical capacity of the subject, how often and severely this occurs, and for how many years the overexertion persists or recurs. This would explain results from studies showing that LBP and other musculoskeletal complaints are higher among children who have to carry their schoolbags for longer periods, (Delele, Janakiraman, Bekele Abebe, Tafese, & Water, ; Dockrell, Blake, et al, ; Dockrell, Simms, et al, ) and may suggest that the weight of schoolbags is less relevant in environments where the children have to walk carrying their schoolbag short distances, than in those where they have to carry them for miles every day to attend class (Delele et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is likely that the key mechanical factor triggering LBP when carrying a schoolbag is not its weight per se, but whether it exceeds the physical capacity of the subject, how often and severely this occurs, and for how many years the overexertion persists or recurs. This would explain results from studies showing that LBP and other musculoskeletal complaints are higher among children who have to carry their schoolbags for longer periods, (Delele, Janakiraman, Bekele Abebe, Tafese, & Water, ; Dockrell, Blake, et al, ; Dockrell, Simms, et al, ) and may suggest that the weight of schoolbags is less relevant in environments where the children have to walk carrying their schoolbag short distances, than in those where they have to carry them for miles every day to attend class (Delele et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan Africa, the reported prevalence of childhood flatfoot in Kenya, Nigeria, and Tanzania is 45.3%, 22.4%, %, and 20.3% respectively [15,16]. Besides, a regional study reported that 7.8% of schoolchildren had ankle and foot pain [17]. Studies had reported several risk factors for flatfoot among children like family history, age, gender, weight, BMI, type of footwear, physical activity, and associated with hypermobility, genu valgum, and heel valgus [1,5,6,12,18].…”
Section: Introductionmentioning
confidence: 99%
“…The term includes minor transient complaints to irreversible damage and disability [11]. The prevalence of MSDs is between 16% and 86% in school children in developed countries, and in the range of 46.3-88.8% in developing countries [12].…”
Section: Introductionmentioning
confidence: 99%